INFORMATION SYSTEM DESIGN SALES OF GOODS IN PT. SUPER POLY - Budi Anggawidjaja; Ir. Fitri Sjafrina, MMSI (Jurnal Sistem Informasi, 1999)
At PT. Poly Super still looks a few obstacles in the process of day-to-day implementation, in this part of the warehouse are still experiencing difficulties in providing sales information.  By using computer tools we can access data quickly. Besides construction work performed on the salespeople who have to move - relocate to the administration, so that inefficient work. With sales information system created to overcome these obstacles by working on one part in carrying out their daily work.